The Role of Social Media Influencers in Cosmetic Marketing: A Systematic Literature Review - Nurdianasari, Rista; Maharani, Shabira; Damarani, Zelika Nidya (Transpublika Publisher, 2025)
The rapid growth of social media has transformed the beauty and cosmetics industry, positioning social media influencers (SMIs) as critical intermediaries between brands and consumers. This study conducts a Systematic Literature Review (SLR) of 37 empirical articles published between 2015 and 2025 to synthesize how influencer credibility, authenticity, and parasocial relationships affect consumer behavior, brand perception, and purchase intention. The review follows PRISMA 2020 and bibliometric protocols using Publish or Perish, Scopus, CrossRef, and Covidence for systematic screening. The findings indicate four dominant research themes: (1) source credibility and influencer attributes, (2) authenticity and parasocial relationships, (3) consumer behavioral outcomes such as brand trust and loyalty, and (4) strategic influencer marketing practices. The results reveal that trustworthiness and authenticity consistently mediate the relationship between influencer credibility and purchase intention, while cultural and contextual factors moderate these effects. Moreover, micro- and nano-influencers are increasingly valued for their authenticity and engagement over macro-influencers with larger audiences. The review concludes that influencer marketing in the cosmetics sector has evolved from transactional promotion to relational advocacy, emphasizing ethical transparency, audience alignment, and sustainable consumer loyalty.